Kerentanan Relatif Beras terhadap Hama Kumbang Bubuk Gabah (Rhyzopertha dominica (F.)) : Susceptibility Relative of Rice to Lesser Grain Borer (Rhyzopertha dominica (F.)) - Hendrival; Khaidir; Hafifah; Nazimah (Universitas Widya Gama Mahakam, 2022)
The lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) is a primary pest that causes damage to stored cereals such as corn, grain, rice, wheat, sorghum, tubers, and starch-containing substrates and packaging made from wood. R. dominica not only cause losses in terms of quantity but also affect quality during the storage period through their feeding activities. The study aimed to determine the level of susceptibility to rice during storage to R. dominica. The research was conducted at the Laboratory of Plant Pest and Disease, Faculty of Agriculture, Malikussaleh University, Aceh which began from November 2019 to February 2020. The study was done in the form of laboratory experiments using a Completely Randomized Design (CRD) nonfactorial with a total treatment of 10 rice varieties. The results of variance analysis using the Duncan Multiple Range test showed that the susceptibility level of rice to R. dominica infestation was classified into moderate category. The highest percentage of weight loss was found in Mekongga varieties (1,95%) while the lowest in Inpari 30 (0,73%)